2021
DOI: 10.1108/ijchm-08-2020-0855
|View full text |Cite
|
Sign up to set email alerts
|

The gateway bug to edible insect consumption: interactions between message framing, celebrity endorsement and online social support

Abstract: Purpose Climate change and global population growth are threatening the sustainability of hospitality food systems. Foodservice organizations are seeking an optimal solution for this problem. The United Nations Food and Agriculture Organization proposed edible insects as a solution, yet the “yuck” factor discourages consumers from actively endorsing this option. Thus, this study aims to find ways to increase consumer acceptance of edible insects. Design/methodology/approach A 2 (message framing: hedonic vs u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…Moreover, these findings also demonstrate that although nonverbal messages in advertisements play a critical role, it is not practical to offer consumers nonverbal messages with “any” verbal messages (Fox et al , 2019; Helberger et al , 2020). Thus, advertisers should grasp the different joint impacts of nonverbal and verbal messages (Legendre and Baker, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these findings also demonstrate that although nonverbal messages in advertisements play a critical role, it is not practical to offer consumers nonverbal messages with “any” verbal messages (Fox et al , 2019; Helberger et al , 2020). Thus, advertisers should grasp the different joint impacts of nonverbal and verbal messages (Legendre and Baker, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the impact of external stimulus (i.e. advertising) on consumption behaviors depends on not only verbal and nonverbal messages from ads but also the social context and consumers’ personal traits, such as social distance (Schreuder et al , 2016; Legendre and Baker, 2021). That is to say, how much consumers attach to their companions could be a critical factor in making decisions concerned with their daily life social interactions (Lee and Youn, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Further research should also aim to develop effective strategies for building positive consumer attitudes towards edible insects. Online social support for the consumption of edible insects has been addressed in only a few papers [ 122 ]. Insect farms need to be regularly controlled to evaluate the impact of insect production on the economy, environment and local communities.…”
Section: Concluding Remarks—the Outlook For Insect Farming Sectormentioning
confidence: 99%
“…Duhan et al (2019) showed how consumer perceptions coupled with those scenarios provide elaborated information, hastening message processing and decision-making. To date, few extant studies (Legendre and Baker, 2021) have investigated the relationship between celebrity-endorsed hospitality experience and customers' attitudinal and behavioral outcomes (such as restaurant advocacy and satisfaction).…”
Section: Introductionmentioning
confidence: 99%